Peran Sentral Kepala Sekolah di Dabin Kaliyitno Kecamatan Dawe Kabupaten Kudus dalam Pelaksanaan Manajemen Berbasis Sekolah - Susanti Susanti; A. Hilal Madjdi; Sudarti Sudarti (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2023)
The Indonesian government seeks to improve education with policies and curriculum changes that support the times. One of the policies implemented is a centralized school-based management system (SBM). MBS gives schools the freedom and responsibility to develop their potential creatively and innovatively. The headmaster has a role as a manager, administrator, supervisor, leader, entrepreneur and motivator. The headmaster in the Kaliyitno Group, Kudus Regency, have carried out these various central roles in the implementation of SBM. This study used a qualitative method with data collection through interviews, observations, and document observation. The results of the study show that headmaster in the Kaliyitno Cluster have succeeded in carrying out central roles in implementing SBM, such as effective management, good administrative services, teacher supervision, good leadership, entrepreneurship, motivation, and creating a conducive climate. It is recommended that headmaster be more intensive in socializing SBM, develop the competence of headmaster on an ongoing basis, and get greater support to increase the success of SBM implementation.